Module-scale analysis of low-salt-rejection reverse osmosis: Design guidelines and system performance. (1st February 2022) - Du, Yuhao; Wang, Zhangxin; Cooper, Nathanial J.; Gilron, Jack; Elimelech, Menachem
Highlights: Module-scale analysis of low-salt-rejection reverse osmosis (LSRRO) is performed. Both membrane properties and operating conditions impact the performance of LSRRO. The stage number of an LSRRO system needs to be optimized. LSRRO can minimize the use of thermal brine concentrators for brine management. LSRRO membranes can be prepared by oxidative treatment of conventional RO membranes. Abstract: Low-salt-rejection reverse osmosis (LSRRO) is a novel reverse osmosis (RO)-based technology that can highly concentrate brines using moderate operating pressures. In this study, we investigate the performance of LSRRO membrane modules and systems using module-scale analysis. Specifically, we correlate the observed salt rejection of an LSRRO module with the water and salt permeabilities of the RO membrane. We then elaborate the impact of membrane properties and operating conditions on the performance of a 2-stage LSRRO, providing design guidelines for LSRRO systems. We further compare the performance of 2-stage and 3-stage LSRRO systems, showing that an LSRRO system with more stages is not always favored due to a larger energy consumption. The performance of a 3-stage LSRRO in treating different feed solutions for minimal/zero liquid discharge (MLD/ZLD) applications is then evaluated. Based on our results, when treating feed waters with a relatively low salinity (e.g., 0.1 M or ∼5, 800 mg L −1 NaCl), the 3-stage LSRRO can achieve a concentrated brine that can be directly sent to the thermal brine crystallizers (i.e., brine concentration > 4 M or ∼240, 000 mg L −1 NaCl), and the corresponding specific energy consumption ( S E C ) is only ∼3 kWh m −3 . When treating feed waters with a relatively high salinity (e.g., 0.6 M or ∼35, 000 mg L −1 NaCl), the brine from the 3-stage LSRRO can be ∼80 % more concentrated compared to that from conventional RO, while the corresponding S E C does not exceed 6 kWh m −3 . Our results demonstrate that LSRRO can substantially advance minimal/zero liquid discharge (MLD/ZLD) applications because it can significantly minimize the use of thermal brine concentrators. We conclude with a discussion on the practicability of LSRRO and highlight future research needs. Graphical Abstract: Image, graphical abstract